2015
DOI: 10.1186/s13075-015-0670-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for progression of clinical osteoarthritis of the knee: a systematic review of observational studies

Abstract: IntroductionWe performed a systematic review of prognostic factors for the progression of symptomatic knee osteoarthritis (OA), defined as increase in pain, decline in physical function or total joint replacement.MethodWe searched for available observational studies up to January 2015 in Medline and Embase according to a specified search strategy. Studies that fulfilled our initial inclusion criteria were assessed for methodological quality. Data were extracted and the results were pooled, or if necessary summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 50 publications
9
102
1
3
Order By: Relevance
“…17 In a recent systematic review, strong evidence for the associations between BMI and clinical progression of knee OA was reported by the authors, 7 which is consistent with the findings presented here. The authors also found strong evidence for the association with comorbidity count, 7 and moderate evidence was found for the association between education level and symptomatic knee OA. 7 In this study a strong association for joint space tenderness, for which the evidence was limited in the systematic review, was found.…”
Section: Comparison With Existing Literaturesupporting
confidence: 82%
See 3 more Smart Citations
“…17 In a recent systematic review, strong evidence for the associations between BMI and clinical progression of knee OA was reported by the authors, 7 which is consistent with the findings presented here. The authors also found strong evidence for the association with comorbidity count, 7 and moderate evidence was found for the association between education level and symptomatic knee OA. 7 In this study a strong association for joint space tenderness, for which the evidence was limited in the systematic review, was found.…”
Section: Comparison With Existing Literaturesupporting
confidence: 82%
“…The authors also found strong evidence for the association with comorbidity count, 7 and moderate evidence was found for the association between education level and symptomatic knee OA. 7 In this study a strong association for joint space tenderness, for which the evidence was limited in the systematic review, was found. 7 The findings related to joint space tenderness are consistent with earlier findings described by Altman and colleagues, and underline the importance of physical examination.…”
Section: Comparison With Existing Literaturementioning
confidence: 70%
See 2 more Smart Citations
“…High quality was defined as a quality score of C9 and low quality \9. The same approach has also been applied in studies on the prognostic factors of knee and hip arthritis [32,33]. All included articles were scored independently by SSAF and RMH.…”
Section: Methodological Qualitymentioning
confidence: 99%